A PRIMER ON THE DIRECTORS’ OVERSIGHT FUNCTION AS A STANDARD OF DIRECTORS’ CONDUCT UNDER THE COMPANIES ACT 71 OF 2008 - Jan Louis Van Tonder (Obiter, 2018)
The recent well publicised corporate scandals and widespread allegations of corporate fraud and corruption in both the private and public sector, which occurred seemingly unnoticed and caused public outrage, prompted this article. Although it is clear that directors should not be passive in their monitoring and oversight function and the notion of a passive director must be discouraged, as such, the oversight function has received little or no attention in South Africa, and is, as a result, not well developed in South Africa. The aim of this article is to provide a preliminary analysis of the content and meaning of the directors’ oversight function as a standard of directors’ conduct and to reconcile the oversight function with the business judgment rule. Section 5(2) of the Companies Act provides that, to the extent appropriate, a court interpreting or applying the provisions of the Companies Act may consider foreign company law. This is complementary to section 5(1), which directs that the Companies Act must be interpreted and applied in a manner that gives effect to the purpose of section 7. In light hereof, the article will refer to the Model Business Corporation Act to assist the research in examining the content and meaning of the oversight function as a standard of directors’ conduct and to reconcile the oversight function with the business judgment rule.